2022
DOI: 10.1038/s41467-022-34859-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure of nucleosome-bound human PBAF complex

Abstract: BAF and PBAF are mammalian SWI/SNF family chromatin remodeling complexes that possess multiple histone/DNA-binding subunits and create nucleosome-depleted/free regions for transcription activation. Despite previous structural studies and recent advance of SWI/SNF family complexes, it remains incompletely understood how PBAF-nucleosome complex is organized. Here we determined structure of 13-subunit human PBAF in complex with acetylated nucleosome in ADP-BeF3-bound state. Four PBAF-specific subunits work togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Histone modification of endothelial cells can reveal information about the regulatory mechanisms of changes in gene expression. Arid1a has been associated with nucleosome composition, histone modification and fate determination 27,34,35 . We examined a range of histone modifications, including H3K4me3, H3K9me3, H3K27me3, H3K27ac, and H3k36me3, where H3K27ac was significantly increased in Arid1a ‐deficient endothelial cells (Figure 5A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Histone modification of endothelial cells can reveal information about the regulatory mechanisms of changes in gene expression. Arid1a has been associated with nucleosome composition, histone modification and fate determination 27,34,35 . We examined a range of histone modifications, including H3K4me3, H3K9me3, H3K27me3, H3K27ac, and H3k36me3, where H3K27ac was significantly increased in Arid1a ‐deficient endothelial cells (Figure 5A,B).…”
Section: Resultsmentioning
confidence: 99%
“…A trace of contaminating SPhos oxide remained that could be removed by rechromatographing and eluting with a shallow gradient of methanol in DCM, yielding apparently pure fractions among those eluting later. 1 (R)-6-(Furan-2-yl)-4-(2-methylpiperidin-1-yl)pyridazin-3-amine (30). The R-enantiomer was synthesized from 39 in the manner described above for 29, although the coupling reaction did not proceed to completion after 18 h. After workup and chromatography, the desired product was obtained in ∼10% yield (12.2 mg, 0.047 mmol).…”
Section: S)-1-(4-(3-amino-6-chloropyridazin-4-yl)-3-methylpiperazin-1...mentioning
confidence: 99%
“…Interestingly, although mSWI/SNF is an NCP-displacing multi protein complex, until recently only SMARCB1 and the ATPase BRG1 25,26 , had been reported as proteins carrying clearly mapped NCP-binding domains. The interaction of PBAF with the nucleosome has been further clarified with the identification of more subunits coming in contact with the nucleosome 19 , but much remains to be discovered about the interactions between mSWI/SNF and its substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the structure, the molecular details of interaction and the function of BCL7 subunits within mSWI/SNF are poorly defined at best. The topological information currently available is limited to the observation that BCL7 proteins make contacts with BRG1, SMARCB1, DPF2, actin and histone H2B 18,19 . Recent studies have reported the cryo-EM structure of the SWI/SNF complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation